Buying conspicuous organic food when it’s crowded: how social crowding and the need for self-expression influence organic food choices - Qiuqin Zheng; Xiaoxia Chen; Haimei Zeng (Frontiers in Sustainable Food Systems)
With an expanding consumer base for organic food globally and a steadily growing interest worldwide, it is important to understand the influencing factors behind organic food preference formation and purchasing decisions. Distinguishing from previous studies, this study focuses on the conspicuousness of organic food consumption and proposes a new concept of conspicuous organic food consumption. This study aims to explore the relationship between social crowding, the need for self-expression, and conspicuous organic food consumption. Through three experimental studies, this study reveals that: (1) social crowding positively influences the consumption of conspicuous organic foods, (2) the need for self-expression plays a mediating role, and (3) self-concept clarity plays a moderating role. Specifically speaking, the conspicuousness leads consumers to increase their choice of organic food under social crowding, with the need for self-expression playing a fully mediating role in this effect. However, this effect only exists among consumers with lower levels of self-concept clarity; when consumers have higher levels of self-concept clarity, the influence of social crowding and non-social crowding on conspicuous organic food consumption does not significantly differ. By highlighting the uniqueness and usefulness of social crowding as an environmental factor, this study can facilitate companies to adjust their organic food marketing strategies to different levels of crowding promptly, thereby expanding organic food consumption.